IMPLEMENTASI ASESMEN PORTOFOLIO DALAM PEMBELAJARAN BAHASA INDONESIA KURIKULUM MERDEKA SISWA KELAS VII DI SMP SWASTA KATOLIK BUDI MURNI 2 - Saruksuk, Hotti Sanogaria Lasmarito; Berman Hutahaean; Candra Ronitua Gultom; Monica Marcelina Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of portfolio assessment in Indonesian language learning under the Merdeka Curriculum for seventh-grade students at SMP Swasta Katolik Budi Murni 2 Medan. The research employed a descriptive qualitative approach with a case study design. The subjects consisted of an Indonesian language teacher, 22 seventh-grade students, and students’ portfolio documents. Data were collected through observation, in-depth interviews, documentation, and open-ended questionnaires, and analyzed using Miles and Huberman’s interactive model. The findings show that the teacher understands portfolio assessment as a continuous evaluation, yet its implementation remains limited to certain writing tasks and has not been fully integrated into daily learning activities. Student reflection and teacher feedback were not optimal, while the main challenges included limited time, students’ discipline, and insufficient facilities. Nevertheless, portfolio assessment was proven to enhance students’ motivation, writing skills, participation, and self-confidence. The study concludes that portfolio assessment is relevant to the principles of the Merdeka Curriculum as it authentically evaluates both process and outcomes of learning. Therefore, teacher training, effective time management, and the development of digital portfolios are needed to optimize its implementation.